Blood Cross-Match Ordering Practices - Madeeha Rehan,Aatika Khalid, Sehar Khaliqe, Sami Saeed,Tariq Butt (Journal of Rawalpindi Medical College, 2016)
Background: To assess blood utilization practices by evaluating the cross-match ordering and transfusion ratio in surgical and nonsurgical patients to avoid unnecessary transfusion and wastage of blood. Methods: In this prospective study patients belonging to age of 1 year to 60 years, which were admitted in Pediatric, Medicine, Surgery, Gynae/OBS / Orthopaeds/ wards were included. Cross-matched to transfusion ratio (C/T ratio), Transfusion probability (%) and Transfusion Index (Ti) for each of these patients was performed during the study period. C/T ratio is used as a measure of the efficiency of blood ordering practice. It should ideally be between 2 and 2.5. We compared our results with the ideal. Results: Requests from 2800 patients were sent to prepare 3547 cross matched units. Of these, 2723 units were transfused. Overall C/T was 1.3, %T 76.7%,Ti 0.9. Of the total cross match requested 44.4% were requested by surgical department including Gynae/OBS, Urology, Neurosurgery, Orthopeads and General surgeries. Out of all surgical departments C/T of Gynae/OBS was 2.5% & of all other surgical departments was 1.7% &Ti o.4. C/T ratio of nonsurgical patients was 1.09. Conclusion: Overall blood utilization was encouraging, but excessive cross-matching with minimal transfusion practice was observed in Gynae/OBS patients which can be minimized by considering transfusion triggers before requesting cross-match.